ETHNOCENTRISM AND CULTURAL INCONGRUITY IN HENRY JAMES’S DAISY MILLER: A STUDY - Dyah. Eko Hapsari, M.Hum (ISSN)
Daisy Miller: A Study (1878), broadly, is an analysis of various tensions between Europe and America. As the title character and her family travel abroad, they are confronted with customs and traditions of old Europe. An independent and stubborn young woman, Daisy Miller is unwilling to accept these old ideas, as do many Americans living abroad. As a representative of a newer, more liberal method of social interaction, she struggles in an old, conservative society. Daisy Miller: A Study focuses on the behavior of its characters in social situations. Most of the action involves Daisy’s social missteps, followed by discussion of those missteps. Characters constantly refer to their social status and are engaged in bettering their places. Those characters that represent the Europeanized-Americans always consult the European culture and its social values as the standard for judging Daisy’s attitudes. Their judgments are based on the European moral values. This means that, there is a kind of ethnocentrism in the way they think that European culture is superior, and this point of view results in cultural incongruity.